Healthcare providers’ knowledge, attitudes and practices on smoking cessation intervention in the Northern Cape - Lizwe C. Muza; Chika K. Egenasi; Wilhelm J. Steinberg; Mathew O. Benedict; Talat Habib; Ferdinand Mampuya; Cornel van Rooyen (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2024)
Background: Clinicians are crucial in encouraging smokers to quit through behavioural or pharmacological smoking cessation interventions. Smokers quit better with professional help. The level of healthcare providers’ (HCPs) knowledge, attitudes and counselling skills related to effective smoking cessation support in the study area remains uncertain.